2008
DOI: 10.1108/13522750810864459
|View full text |Cite
|
Sign up to set email alerts
|

YouTube: an opportunity for consumer narrative analysis?

Abstract: Purpose -The aim of the paper is to discuss a possible extension of narrative analysis to a new medium of expression of consumer behaviour, specifically YouTube. Design/methodology/approach -Marketing and consumer behaviour studies often apply narrative analysis to understand consumption. The consumer is a source of introspective narratives that are studied by scholars. However, consumption has a narrative nature in itself and consumers are also storytellers. YouTube is a new context in which subjects tell sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 29 publications
(39 reference statements)
1
73
1
10
Order By: Relevance
“…The literature review showed that the analysis of the videos and the comments submitted to that platform and the comments thereof are a good source for recognizing consumers' needs and market trends (Pace 2008;Wendt, Griesbaum, and Kölle 2016). This is also confirmed by our study.…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 76%
See 1 more Smart Citation
“…The literature review showed that the analysis of the videos and the comments submitted to that platform and the comments thereof are a good source for recognizing consumers' needs and market trends (Pace 2008;Wendt, Griesbaum, and Kölle 2016). This is also confirmed by our study.…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 76%
“…YouTube is also a sns, which is used to a significant extent in e-wom. It is considered to be a repository of knowledge about markets, consumers, products, and services because information shared on YouTube in the form of videos comes from users who are also consumers (Pace 2008;Wendt, Griesbaum, and Kölle 2016). Vloggers often record videos and publish them on YouTube in order to recommend products they bought and which are of good quality or warn other users against low quality products.…”
Section: Sns In Communication (C) Within the Context Of Cmc Theorymentioning
confidence: 99%
“…Such videos are commented on by other users. This means that the opinions of many users, often from remote parts of the world, can be collected and accessed (Pace 2008;Madden, Ruthven, and McMenemy 2013). Numerous studies are conducted on the analysis of comments placed on YouTube under a particular video.…”
Section: Sns In Communication (C) Within the Context Of Cmc Theorymentioning
confidence: 99%
“…The literature review showed that the analysis of the videos and the comments submitted to that platform and the comments thereof are a good source for recognizing consumers' needs and market trends (Pace 2008;Wendt, Griesbaum, and Kölle 2016). This is also confirmed by our study.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation